Modify The Led Lights By Adding Pir Sensor As A Motion Sensor - Permana, Angga Aditya; Pradipta, Allan; Henry, Amir Acalapati; Sufyan, Ammar; Maskurudin, Muhamad; Syafiq, Zahra (International Journal of Science, Technology & Management, 2023)
Motion sensor lights have become a popular solution to optimize lighting usage in various spaces and environments. This article explores the concept and advantages of motion sensor lights, which are capable of detecting human motion and automatically controlling illumination. Motion sensor lights use PIR sensors to detect human movement, triggering a relay module as a switch to turn the lights on or off. The primary benefit of motion sensor lights is energy efficiency, reducing unnecessary power consumption. The article also explains how to create motion sensor lights using simple tools and easy-to-follow steps. Consequently, readers can grasp the fundamental concept of motion sensor lights and have a practical guide to make them on their own. Through the research conducted, a modification of regular LED lights into LED lights that can function with a PIR sensor has been achieved through several experiments.